Front Cover: Water‐Mediated Structural Transformations of CuII 5‐Halonicotinates Coordination Networks with Distinct Mechanisms (Chem. Eur. J. 53/2017). Issue 53 (21st July 2017) - Li, Cheng‐Peng; Zhou, Hang; Ju, Yue; Du, Miao
Abstract : Three types of mechanisms regulated by halogen substituent effect, namely single‐crystal to single‐crystal transformation as well as "core‐to‐core" and "core‐on‐shell" processes, have been confirmed for elucidation of the "black box" during structural transformations of dynamic crystalline materials. The combination of time‐lapse optical microscopy and X‐ray single‐crystal diffraction techniques provides a convenient and straightforward approach to reveal the transformation mechanisms. More information can be found in the Communication by M. Du et al. onpage 12985 .